Synthesis, monoamine oxidase inhibitory activity and computational study of novel isoxazole derivatives as potential antiparkinson agents. (April 2019) - Agrawal, Neetu; Mishra, Pradeep
Graphical abstract: Highlights: Synthesis of some phenylisoxazole carbohydrazides and evaluation of their in vitro MAO inhibitory activity. Among the synthesized compounds, 6c showed significant MAO-B inhibitory activity and selectivity over MAO-A. ADMET properties of all the synthesized were predicted. Docking studies were carried out to understand the possible binding modes. Motor behavioural assessment was done for most potent compound 6c. Abstract: Monoamine oxidase (MAO) enzymes are one of the most promising targets for the treatment of neurological disorders. A series of phenylisoxazole carbohydrazides was designed, synthesized and screened for both MAO-A and MAO-B inhibition using Amplex Red assays. None of the compounds inhibited the MAO-A activity while most of them significantly inhibited MAO-B in the micromolar to nanomolar range. Among them, the compound N '-(4-methylbenzylidene)-5-phenylisoxazole-3-carbohydrazide (6c ) exhibited the most potent inhibitory activity towards MAO-B. Enzyme kinetic studies revealed the reversible and competitive nature of compound6c towards MAO-B inhibition. The results of the enzyme inhibition assay were in agreement with molecular docking study, in which compound6c displayed a strong binding affinity for MAO-B with a docking score of -10.98 Kcal/mol. In order to explore the neuroprotective effect of compound6c, MPTP-induced mouse model for Parkinson's disease was used, and motor behavioural assessment of experimental animals was carried out. The compound6c was able to significantly prevent the MPTP-induced neurotoxicity as revealed by improvement in gait behaviour in footprint test and increase in grip strength score in horizontal wire test. Thus, phenylisoxazole carbohydrazides can be promising leads in the development of potent, selective and reversible MAO-B inhibitors for the treatment of Parkinson's disease.